MODERN ASPECTS OF COST MANAGEMENT OF UKRAINIAN ENTERPRISES - Svitlana Kulakova; Anastasiia Tkachenko; Mariia Razno (Фінансово-кредитні системи: перспективи розвитку., 2023)
Now, in difficult economic conditions in Ukraine, the issue of effective cost management is becoming relevant for enterprises, taking into account the opportunities to stimulate resource savings, forecasting and controlling costs according to the “Expenses-output-profit” system.